Measuring gait parameters from structural vibrations. (31st May 2022) - Davis, Benjamin T.; Bryant, Brianna I.; Fritz, Stacy L.; Handlery, Reed; Flach, Alicia; Hirth, Victor A.
Abstract: Measuring gait parameters (e.g. speed, cadence, step duration) accurately is invaluable for evaluation during treatment of older adults who struggle with disability onset, disease progression, balance, and injurious falls. Traditionally stopwatches or timing gates are used to measure gait speed in clinical settings, and these are limited to measuring gait speed. Other wearable and non-wearable technologies offer the ability to measure additional gait parameters though patients are known to walk differently with the devices and even tend to slow down before engaging with a non-wearable such as a floor mat. Floor vibrations are a promising option to measuring gait parameters while not being intrusive and not requiring line-of-sight to the patient for measurements. This paper presents methodology for extracting gait parameters using vibrations with comparisons to APDM Wearable Technologies Mobility Lab sensors and stopwatch measurements. Performance is examined across 97 participants for self-selected speed forward, full speed forward, and backwards walks at three different testing sites for a total of 1039 walks. Gait speed vibrations measurements demonstrated excellent reliability with APDM Mobility Lab (ICC: 0.98; 99% CI: 0.01 ± 0.01 m/s) and stopwatch (ICC: 0.97; 99% CI: −0.01 ± 0.01 m/s) measurements. Similar excellent results are reported for cadence, gait cycle duration, step duration, and stride length parameters. Highlights: Measuring gait parameters is valuable for evaluation during older adult treatment. Gait parameters can be measured using structural vibrations caused by walking. Vibration measurement methodology comparison to APDM. Proposed methodology is a viable alternative to conventional measurement approaches.